Mediating the role of employee willingness to perform between career choice and employee effectiveness (case study in public sector universities of Pakistan) - Raza, Ali; Wan Mohd Noor, Wan Shakizah; Fareed, Muhammad (IJICC, 2020)
Following the upsurge and development in the globalized and emerging economies, commercial misunderstanding and disputes transcending national borders may also be on the rise. Such disputes can hamper the economic activities and operation within those emerging economies, in particular those activities related to foreign direct investment. National legal mechanisms may not be attractive to international investors. Instead, international commercial arbitration (ICA) could be a preferred choice of foreign investors through which contractual disputes can be resolved via an independent forum because it helps to foster market efficiency, facilitate foreign direct investment and protect the interest of foreign investors. To offer insights on this issue theoretically and empirically, this paper presents a logic-based and empirically- based conceptual discussion to investigate the influence of ICA on FDI, in particular its application in the context of Algeria and the importance of domestic courts’ execution of arbitral awards. The paper finds that ICA is indispensable to contractual conflict resolution and can consequently assist FDI inflows into the country that entrenches it. Algeria may increase FDI inflows by strengthening the legal framework for arbitration through the enhancement of national laws relating to ICA and guaranteeing their effective execution and enforcement by the local judicial system.